Post-processing for convolutive blind source separation - Aichner, Robert; Zourub, Meray; Buchner, Herbert; Kellermann, Walter (2006 IEEE International Conference on Acoustics, Speech and Signal Processing, ICASSP 2006, 2006)
Convolutive blind source separation (BSS) aims at separating point sources from mixtures picked up by several sensors. In real-world environments moving speakers, background noise and long reverberation are encountered which often degrade the performance of BSS algorithms. In such cases, the application of a post-filter can improve the output signal quality by suppression of residual crosstalk and of background noise. In this paper we propose a novel technique to estimate the necessary power spectral densities of the cross-talk components and present a robust system which allows to further suppress both, the remaining interference from point sources and the background noise. Experimental results show the benefit of this post-processing method in realistic environments. © 2006 IEE